A HERMENEUTIC ANALYSIS OF ISLAMIC EDUCATIONAL VALUES IN HINDIA'S 'MEMBASUH' SONG AS A MEDIUM FOR MORAL EDUCATION - Ramadhani, Dwi; Rizky Erdanu, Albrillyant (Almustofa Journal of Islamic Studies and Research, 2025)
This study aims to analyze the internalization of Islamic educational values in the song “Membasuh” by Hindia through a hermeneutic approach. The song was chosen because it contains moral and spiritual messages that align with the principles of Islamic teachings, even though they are conveyed through a popular cultural medium. This research employs a descriptive qualitative approach using hermeneutic analysis to interpret the implicit meanings embedded in the lyrics. The primary data consist of the lyrics of “Membasuh,” while the secondary data are drawn from literature on Islamic education, hermeneutic theory, and relevant Qur’anic verses and hadiths. The findings reveal that the song “Membasuh” embodies eight core Islamic educational values: sincerity (ikhlās), patience (ṣabr), asceticism (zuhd), mutual help (ta‘āwun), compassion (rahmah), forgiveness (‘afw), excellence (iḥsān), and steadfastness (istiqāmah). These values reflect the spiritual journey of human beings toward moral awareness and servitude to Allah. The song also holds pedagogical relevance, as it can be used as a reflective medium in Islamic moral education, particularly for young generations who are familiar with digital media and popular music. In conclusion, Hindia’s work demonstrates that Islamic educational values can be internalized in contextual and humanistic ways through artistic and cultural expression.